Specyfika transakcji sekurytyzacyjnych przeprowadzanych w Polsce - Berlik, Anna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Securitisation is a very popular transaction in well developed markets. In Poland this transaction appeared only a few years ago and in the initial period did not attain high popularity. Currently it is becoming a tool which is used by banks to improve some indicators or to reduce income tax. The law specific for the Polish market has a significant impact on transaction's characteristics. It is also a factor which supports foreclosure market development. The article presents differences between traditional securitisation which occurs over the world and the Polish transactions. It is also an attempt to answer the question if Polish securitisation may be called securitisation. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 35-45